Relationship between the levels of awareness and knowledge of periodontitis in diabetic patients at a Dental Hospital during the COVID-19 pandemic - Nathania, Irene; Harsas, Nadhia Anindhita; Natalina; Tadjoedin, Fatimah Maria (Dental Journal (Majalah Kedokteran Gigi), 2023)
Background: Diabetes mellitus (DM) and periodontitis are the most prevalent human diseases. Diabetes worsens the periodontal condition, but periodontitis also hampers glycemic control in diabetic patients. Based on staging and grading, the latest periodontitis classification puts DM as one of the grade modifiers. Periodic periodontal maintenance prevents reinfection and could help people with diabetes maintain effective glycemic control. Dental health education and periodontal disease awareness are crucially needed for diabetic patients, especially during the pandemic. Purpose: This study aimed to examine the relationship between levels of awareness and knowledge of periodontitis in diabetic patients during the COVID-19 pandemic. Methods: A closed-ended questionnaire was distributed to new patients referred to the Periodontology Clinic of the Dental Hospital of Universitas Indonesia. Patients' data were collected during the COVID-19 pandemic from January to June 2021. Results: Eighty-four patients participated, of which 34.5 % were diabetic patients with periodontitis. Statistically, significant differences (P < 0.05) were found between levels of awareness and knowledge of periodontitis among diabetic patients and nondiabetic patients (both groups are suffering periodontitis). Awareness and knowledge of periodontitis are inversely correlated with their current clinical periodontal status, therefore patients with less awareness and knowledge have more severe periodontitis. Conclusion: Lack of awareness and knowledge of periodontitis was found among both nondiabetic and diabetic periodontitis patients. Dental health education is required to improve understanding and awareness of the relationship between periodontitis and DM.